Gender-related differences in long-term outcome among high-risk patients with myocardial infarction treated invasively - Sarek, Julita; Paczkowska, Anita; Wilczyński, Bartosz; Francuz, Paweł; Podolecki, Tomasz; Lenarczyk, Radosław; Średniawa, Beata; Kalarus, Zbigniew; Kowalczyk, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction : Treating acute myocardial infarction (AMI) with percutaneous coronary intervention (PCI) has an impact on improving long-term outcome. However, patients with other comorbidities are challenging, and are considered as a high-risk population. Aim : To assess gender-related differences in long-term prognosis after AMI among high-risk patients. Material and methods : The single-center registry encompassed 4375 AMI patients treated with PCI. The following high-risk groups were selected: age > 70 group (n = 1081), glomerular filtration rate < 60 group (GFR n = 848), diabetes mellitus (DM) group (n = 782), low ejection fraction (EF) group (n = 560) defined as EF < 35%, and incomplete coronary revascularization (ICR) group (n = 2008). Within each group, comparative analysis of long-term mortality with respect to gender and age was performed. Results : There were no significant differences in long-term mortality with respect to gender among groups with age > 70 (29.0% vs. 30.3%) and GFR < 60 (37.2% vs. 42.3%) (both p = NS respectively for men vs women). In the DM group (24.8% vs. 30.8%; p = 0.06) and EF < 35% group (36.3% vs. 44.5%; p = 0.07) there was a trend towards significance. The ICR group showed a higher mortality rate with respect to gender (19.7% vs. 27.3%; p < 0.001). Differences in survival assessed by the log-rank test were significant among ICR and EF < 35% groups. Conclusions : Female gender is related to higher long-term mortality among high-risk groups, but a statistically significant difference was observed only in patients with ICR and those with EF < 35%. Female gender may be associated with worse prognosis in diabetic patients, but it needs evaluation. However, worse prognosis in women was not independent and was associated mainly with other comorbidities and worse clinical characteristics.